Xanthine oxidase inhibition attenuates insulin resistance and diet-induced steatohepatitis in mice - Nishikawa, Tomoki (Sci Rep, 2020)
Hyperuricemia drives the development of nonalcoholic fatty liver disease (NAFLD). Pharmacological inhibition of xanthine oxidase (XO), a rate-limiting enzyme for uric acid (UA) production, has been demonstrated to improve hepatic steatosis in diet-induced obese mice. However, it remains unclear whether inhibition of XO improves nonalcoholic steatohepatitis (NASH), a more advanced form of NAFLD, in terms of both liver inflammation and fibrosis. Here, we investigated the effects of febuxostat and allopurinol, two XO inhibitors clinically used for gout, on a mouse model of NASH. Furthermore, we conducted a single-arm, open-label intervention study with febuxostat for NAFLD patients with hyperuricemia. Despite a similar hypouricemic effect of the XO inhibitors on blood UA level, febuxostat, but not allopurinol, significantly decreased hepatic XO activity and UA levels in the NASH model mice. These reductions in hepatic XO activity and UA levels were accompanied by attenuation of insulin resistance, lipid peroxidation, and classically activated M1-like macrophage accumulation in the liver. Furthermore, in NAFLD patients with hyperuricemia, treatment with febuxostat for 24 weeks decreased the serum UA level, accompanied by reductions in the serum levels of liver enzymes, alanine aminotransferase and aspartate aminotransferase. XO may represent a promising therapeutic target in NAFLD/NASH, especially in patients with hyperuricemia.